Internal erosion and simplified breach analysis: (upgraded version 2012) - Sadhu, Vijay (Kansas State University, 2012)
In recent years, headline news has been overwhelmed with stories about dam and levee failures including the 2005 levee breaches in New Orleans and the 2006 Kaloko Damfailure in Hawaii that resulted in seven deaths. Since 2000, state and federal agencies have reported 92 dam failures in the United States to the National Performance of Dams Program. Incidents such as these have brought both national and worldwide attention to the need for improved flood warning systems and breach prediction tools for dam embankment and levee failures. (G. J. Hanson, 2010) IESIMBA 2012 is an upgraded version of SIMBA, which has been upgraded from VB6 to C#.NET. The Microsoft Windows-based SIMplified Breach Analysis software (SIMBA) was developed by the USDA Agricultural Research Service in cooperation with Kansas State University. The software was developed for the purpose of analyzing internal erosion, earth embankment breach test data and extending the understanding of the underlying physical processes of breach of an overtopped earth embankment. It is a research tool that is modified routinely to test the sensitivity of the output to various sub-models and assumptions. This software is a test version for use in validation testing of the simplified breach model based on stress and mass failure driven headcut movement. It runs under Microsoft Windows 98SE, Windows 2000, NT, XP, or Vista. The following Input Screens are used to guide the user through development of input data sets.  Model Properties , Dam Profile , Structure Table, Spillway Rating and Hydrograph Data After an input data set has been entered, the data is saved and simulation can be performed on the data stored in memory at any time by selecting Build option. Input and output files are stored in a fixed ASCII text format. The results of the simulation can be viewed in graphical format which are of interest to the researchers at Oklahoma State University, Stillwater by selecting View option.
Keywords: IESIMBA; Internal erosion; vb6 to c#; Embankment overtoppings; Hydrologic Sciences (0388); Information Technology (0489)